The Influence of Perceived Value and Promotion on Purchase Decisions at XYZ Bakery - Rd. Andi Rifai Solihin; Henricus Kurniawan Elang Kusumo; Wulan Meiaya Wowor (Riviera Publishing, 2025)
The objective of this study is to evalutate and analyze the influence of Perceived Value and Promotion on Consumer Purchase Decisions of XYZ bakery. The bakery industry in Indonesia is rapidly developing, especially after the Covid-19 pandemic. The rapid growth has made competition in the bakery industry increasingly tight. The bakery industry is developing not only on a large industrial scale but also on a small and medium scale bakery. To win the business competition, a good understanding of the factors that influence consumer purchasing decisions is needed. This study uses a deductive quantitative approach. The sampling technique in this study is convenience sampling. The population is consumers of the supermarket where XYZ bakery is located. Data collection was carried out by distributing questionnaires online via Google Form. This study uses indicators to measure the influence of the variables studied. From the distribution of questionnaires, a sample of 157 respondents was obtained who were consumers of supermarket where XYZ bakery is located from all over Indonesia.. This study uses the SEM-PLS (Structural Equation Modeling-Partial Least Square) analysis technique with the Smart PLS 4 program as a test tool. The analysis results indicate that both of the independent variables, either Perceived Value or Promotion significanty influence purchase decisions. This indicates that improved value perception and more intensive promotions can significantly increase sales.